Study of the Possibility of Honey Wine Production Using New Active Dry Yeasts and Yeasts Derivatives - Bakhshetsyan, Sh. A.; Gevorgyan, E. R.; Mikayelyan, M. N. (ՀԱԱՀ հիմնադրամ)
The current article is dedicated to the study of the possibility of obtaining alcoholic beverages made by fermenting natural honey (honey wine) using different types of dry active yeast and yeast autolysis derivatives. The data obtained from the results of the research will be interesting both from the scientific and production point of view and allow us to conclude that the selected yeasts can be used for the production of such alcoholic beverages.
Keywords: Food Science and Technology